KUALITAS CHOCOCHIPS COOKIES DENGAN INOVASI SUBSTITUSI UBI JALAR PUTIH - Muharani, Arfiona; Holinesti, Rahmi; Gusnita, Wiwik; Anggraini, Ezi (Ensiklopedia of Journal, 2025)
Abstract: Cookies are a type of snack that is popular in all circles. However, excessive use of wheat flour can negatively impact health due to its gluten content. This study aims to analyze the effect of white sweet potato substitution as a partial substitute for wheat flour in the manufacture of chocochips cookies. This experimental study used a complete randomized design with four white sweet potato substitution treatments (0%, 15%, 30%, and 45%) and three repetitions. Product quality evaluation was carried out through organoleptic testing by 15 semi-trained panelists with a focus on shape, color, aroma, texture, and taste attributes. Data were analyzed using ANAVA and followed by the Duncan test while F-hitung > F-Tabel at the 5% level . The results showed that white sweet potato substitution had a significant effect on shape quality (neat), color,  and taste (sweet)  with an F-count value of 6,21 each; 6,24; and 6,21 > F-table 2.83, but had no significant effect on color, aroma, creamy texture, sweetness, and chocolate taste. The optimal treatment was found in the 30% substitution resulting in cookies with a neat shape (4.33), uniform shape (3.84), a creamy texture (4.31), and a strong chocolate flavor (4.49). This study shows that white sweet potatoes can effectively substitute some wheat flour in the manufacture of chocochips cookies, creating functional food products based on local commodities with sensory qualities that are acceptable to consumers. This research supports the development of healthier snack alternatives while promoting the use of local ingredients to reduce dependence on imported wheat flour.Keywords: Chocochips cookies, White Sweet Potato, Substitution, Quality.